Thalidomide attenuates learning and memory deficits induced by intracerebroventricular administration of streptozotocin in rats - ELÇİOĞLU, HATİCE KÜBRA; KABASAKAL, LEVENT (TAYLOR & FRANCIS LTD, 2013)
Neuroinflammatory responses caused by amyloid beta (A beta) peptide deposits are involved in the pathogenesis of Alzheimer's disease (AD). Thalidomide has a significant anti-inflammatory effect by inhibiting TNF-alpha, which plays role in A beta neurotoxicity. We investigated the effect of thalidomide on AD-like cognitive deficits caused by intracerebroventricular injection of streptozotocin (STZ). Intraperitoneal thalidomide was administered 1 h before the first dose of STZ and continued for 21 days. Learning and memory behavior was evaluated on days 17, 18 and 19, and the rats were sacrificed on day 21 to examine histopathological changes. STZ injection caused a significant decrease in the mean escape latency in passive avoidance and decreased improvement of performance in Morris water maze tests. Histopathological changes were examined using hematoxylineosin and Bielschowsky staining. Brain sections of STZ treated rats showed increased neurodegeneration and disturbed linear arrangement of cells in the cortical area compared to controls. Thalidomide treatment attenuated significantly STZ induced cognitive impairment and histopathological changes. Thalidomide appears to provide neuroprotection from the memory deficits and neuronal damage induced by STZ.
Keywords: Alzheimer; streptozotocin; thalidomide; NECROSIS-FACTOR-ALPHA; NITRIC-OXIDE; TNF-ALPHA; COGNITIVE IMPAIRMENT; OXIDATIVE STRESS; BRAIN; DYSFUNCTION; INHIBITION; PREVENTS; INJURY